Phenylketonuria mutation analysis in Northern Ireland: a rapid stepwise approach. - Zschocke, J (1995)
We present a multistep approach for the rapid analysis of phenylketonuria (PKU) mutations. In the first step, three common mutations and a polymorphic short tandem repeat (STR) system are rapidly analyzed with a fluorescent multiplex assay. In the second step, minihaplotypes combining STR and VNTR data are used to determine rare mutations likely to be present in an investigated patient, which are then confirmed by restriction enzyme analysis. The remaining mutations are analyzed with denaturant gradient-gel electrophoresis and sequencing. The first two steps together identify both mutations in 90%-95% of PKU patients, and results can be obtained within 2 d. We have investigated 121 Northern Irish families with hyperphenylalaninemia, including virtually all patients born since 1972, and have found 34 different mutations on 241 of the 242 mutant alleles. Three mutations (R408W, I65T, and F39L) account for 57.5% of mutations, while 14 mutations occur with a frequency of 1%-6%. The present analysis system is efficient and inexpensive and is particularly well suited to routine mutation analysis in a diagnostic setting.